Exploratory factor of green entrepreneurial intention towards sustainable startup operation - Bakri, Mohammed Hariri; Widjajanti, Kesi; Abdul Rashid, Nurulizwa; Al-Shami, Samer Ali Hussein; Sugiyanto, Eviatiwi Kusumaningtyas; Md Razak, Mohamad Idham; Mat Rasid, Ahmad Mujahid; Ismail, Albert Feisal @ Muhd Feisal (Learning Gate, 2024)
This study tries to identify the factors influencing sustainability in green entreperenurial start-up. Thus, the goal of the research was to recognize the factors influencing sustainability in green entreperenurial start-up., use the Theory Planned Behaviour approach to analyze the interrelationship among these factors and develop conceptual startup green entreperenurial framework using Structural Equation Modeling. As a result, this goal will assist start-up industry managers and practitioners in better understanding the interactions of enablers and identifying critical enablers that influence the sustainability in green entreperenurial start-up. A knowledge gap exists in how startups, especially in developing economies with less institutional support, can navigate sustainability challenges. There's a clear need for detailed empirical research to explore into these issues. In research methodology side It also emphasizes the importance of ensuring research validity through methods like AMOS-SEM for robustness checks in the models. The researcher could intgrate other theory to measure sustainable business acceptance. Previously the study focusses on sustainability in start-up operations 4.0 but the researcher extends the research on Green entrepreneurial Intention toward Sustainable Startup operations.